Znaczenie pracy zawodowej dla matek dzieci z niepełnosprawnością intelektualną - Gałuszka, Izabella; Ochman, Agnieszka (Kultura-Społeczeństwo-Edukacja, 2023)
Professional work for mothers of children with disabilities is described in the literature as a buffer factor that allows them to achieve a sense of satisfaction and self-realization. At the same time, mothers who want to return to this activity after maternity or parental leave encounter numerous difficulties, leading to resignation from further search. As a result, they most often switch to various types of benefits, dealing with the care and upbringing of their child. The aim of the article is to present the results of research on the importance of professional work for mothers of children with severe intellectual disabilities. The research studies determined the percentage of professionally active parents, the mother’s sense of satisfaction with her professional status, as well as the impact of the child’s disability on this activity and the relationship between professional work and parental attitude presented by the mother.